A19 NOVEL HLA-DQ2 TRANSGENIC MICE DEVELOP GLUTEN-IMMUNOPATHOLOGY FOLLOWING GLUTEN SENSITIZATION. (26th February 2020) - Clarizio, A V; Galipeau, H J; Jury, J; Rondeau, L; Godbout, J; Williams, L; Anderson, B; Verdu, E
Abstract: Background: Celiac disease (CeD), an autoimmune and chronic inflammatory enteropathy triggered by the ingestion of gluten, is associated with HLA-DQ2 (~90%) and, to a lesser extent, HLA-DQ8. We previously characterized a humanized mouse model of gluten sensitivity that expresses the HLA-DQ8 allele, and that develops mild innate and adaptive immune pathways related to DQ8+ CeD patients. Gluten peptides recognized in the context of DQ2 differ from those bound to DQ8 molecules and homozygous carriage of HLA-DQ2 provides higher risk for CeD development. Thus, characterization of a transgenic HLA-DQ2 model would allow for the investigation of disease pathways that affect the majority of celiac patients. Aims: Our aim was to determine gluten-immune responses and small intestinal pathology in C57BL/6 mice humanized with the HLA DR3-DQ2 gene. Methods: To break oral tolerance to gluten, DR3-DQ2 mice were orally sensitized with gliadin (5mg/mL) and cholera toxin (CT; 2.5mg/mL) before being challenged with gluten (10mg/mL) for three weeks. Non-sensitized DR3-DQ2 controls mice received CT and a sham challenge. To determine the effects of long-term exposure to gluten, gliadin sensitized DR3-DQ2 mice were placed on a gluten-containing diet for twelve weeks. Controls were given CT and remained on a gluten-free diet. Pathology was evaluated by CD3+ intraepithelial lymphocytes (IELs) counts; villus-crypt (V/C) ratios. Gluten-induced immune responses were evaluated by anti-tissue transglutaminase-2 (tTG) and anti-gliadin antibodies, inflammatory gene expression by Nanostring Technology, and CD4+ T cell proliferation using flow cytometry. Intestinal permeability was measured in vitro by Ussing Chamber. Results: DR3-DQ2 mice that were sensitized and challenged with gluten for three weeks had higher IEL counts, lower V/C ratios, higher anti-gliadin and tTG antibodies, which are used in the serological diagnosis of the disease. Gluten sensitized mice also has higher expression of pro-inflammatory genes, and an induction of gluten specific T cells, but no changes in permeability compared to control mice. DR3-DQ2 mice given a gluten-containing diet for 12 weeks also had higher IEL counts, lower V/C ratios, and higher anti-gliadin and tTG antibodies, but had no changes in permeability compared to controls. Conclusions: These results indicate that mice humanized with the HLA DR3-DQ2 gene show innate and gluten-specific immune responses following sensitization. Thus, mice expressing HLA-DQ2 represents a novel model of gluten sensitivity that can be used to investigate celiac disease pathways related to gluten peptide repertoire that binds to DQ2 MHC class II, encoded by the HLA gene expressed by the majority of celiac patients. Supported by CIHR to EFV and OGS to AVC Funding Agencies: CIHROGS